Endophytic bacteria of clove (Syzygium aromaticum L.) leaves produce metabolites with antioxidant and anti-aging properties - Larasati Arum Utami, Wulan Tri Wahyuni,, Nisa Rachmania Mubarik, Rika Indri Astuti, (Journal of Applied Pharmaceutical Science, 2023)
Endophytic bacteria would become a potential source of metabolites similar to the host plants. Clove (Syzygium aromaticum L.) leaf extract was proven to have antiaging and antioxidant properties. Therefore, this study aimed to identify clove endophytic bacteria and determine the antiaging properties as well as the metabolite profile of the corresponding extract. Antioxidant activity was evaluated in vitro by 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay. Antiaging and mitochondria activities were tested at the cellular level using yeast Schizosaccharomyces pombe as a model. Six isolates of clove endophytic bacteria were isolated using a 0.2 mM H2O2-containing medium. Isolate Bacillus cereus DCN1 was found more viable against strong oxidative stress (>4 mM H2O2), thus suggesting the ability of the isolate in inducing and activating a notable oxidative stress response. However, the ethyl acetate extract of DCN1 (EAN) has low DPPH radical scavenging activity (IC50 value of 262.27 μg/ml). Yet, EAN could extend the life span of S. pombe, likely by increasing mitochondrial activity for the induction of adaptive-mitochondrial reactive oxygen species signaling. Based on metabolite profiling analysis using LC-MS/MS, the EAN contained gallic acid, (epi)-gallocatechin, kaempferol, kaempferol 3-o-(6”-malonyl-glucoside), and rutin. Our data suggest that EAN shows antiaging potential at cellular levels, which is promising as a source of formulation of biopharmaceutical or cosmeceutical products.